KOMUNIKASI TERAPEUTIK DALAM DAKWAH: KAJIAN LITERATUR TENTANG PENDEKATAN EMPATIK DALAM PENYAMPAIAN NILAI ISLAM - Dinar Annisa (AL-MUTSLA, 2026)
This study examines the concept of therapeutic communication in the context of Islamic da'wah through a literature study approach. The study aims to identify therapeutic communication principles relevant to da'wah practice, analyze empathic approaches as a primary component in conveying Islamic values, and formulate an integrative model of therapeutic da'wah communication. Using a systematic literature review method of 35 sources published between 2019 and 2025 from nationally and internationally accredited journals and relevant books, this study finds that therapeutic communication grounded in empathy, genuineness, and unconditional acceptance has strong resonance with da'wah principles in Islam. Findings indicate that empathic approaches in da'wah not only enhance the effectiveness of religious message delivery, but also contribute to the formation of meaningful da'i-mad'u relationships, encourage intrinsic value change, and strengthen the spiritual dimension of mad'u. The therapeutic da'wah communication model formulated encompasses six main principles: fitrah-based empathy (tafa'ul), da'wah authenticity, unconditional positive regard, active listening (sama'), Islamic nonverbal communication, and orientation toward human fitrah. This study contributes to the development of contemporary da'wah scholarship that integrates humanistic psychological approaches with Islamic values.